Natural variation of root hydraulics in Arabidopsis grown in normal and salt-stressed conditions - Sutka, Moira Romina (2011)
To gain insights into the natural variation of root hydraulics and its molecular components, genotypic differences related to root water transport and plasma membrane intrinsic protein (PIP) aquaporin expression were investigated in 13 natural accessions of Arabidopsis (Arabidopsis thaliana). The hydraulic conductivity of excised root systems (Lpr) showed a 2-fold variation among accessions. The contribution of aquaporins to water uptake was characterized using as inhibitors mercury, propionic acid, and azide. The aquaporin-dependent and -independent paths of water transport made variable contributions to the total hydraulic conductivity in the different accessions. The distinct suberization patterns observed among accessions were not correlated with their root hydraulic properties. Real-time reverse transcription-polymerase chain reaction revealed, by contrast, a positive overall correlation between Lpr and certain highly expressed PIP transcripts. Root hydraulic responses to salt stress were characterized in a subset of five accessions (Bulhary-1, Catania-1, Columbia-0, Dijon-M, and Monte-Tosso-0 [Mr-0]). Lpr was down-regulated in all accessions except Mr-0. In Mr-0 and Catania-1, cortical cell hydraulic conductivity was unresponsive to salt, whereas it was down-regulated in the three other accessions. By contrast, the five accessions showed qualitatively similar aquaporin transcriptional profiles in response to salt. The overall work provides clues on how hydraulic regulation allows plant adaptation to salt stress. It also shows that a wide range of root hydraulic profiles, as previously reported in various species, can be observed in a single model species. This work paves the way for a quantitative genetics analysis of root hydraulics.